Neck/shoulders pain and its relation to the use of tv/computer/videogame and physical activity in school students from Bauru - Alberto De Vitta; Débora de Melo Trize; Alexandre Fiorelli; Letícia Carnaz; Marta Helena Souza De Conti; Sandra Fiorelli de Almeida Penteado Simeão
Objective The objective was to determine the prevalence of musculoskeletal pain in the neck/shoulders of school children and its relationship with the level of physical activity and sedentary activities (time spent on TV and computer and/or video game). Materials and methods We conducted a cross-sectional study with a sample of 524 5th to 8th grade students (278 boys and 246 girls), enrolled in all five urban elementary schools in the municipality of Bauru (SP), aged between 10 and 14 years old. Sociodemographic data, sedentary activities - time spent on TV and computer and/or videogame - and level of physical activity - was collected through a Physical Activity Questionnaire for Children (PAQ-C). Results The results showed that the prevalence of localized pain in the neck/shoulders was of 30.1% for boys and girls. It was also found that there is a predominance of onset of pain reported in neck/shoulders in boys related to the frequency and amount of hours a day watching TV and hours on the computer, whereas in girls the association was with frequency and amount of hours they watch TV daily. Conclusions It can be concluded that the pain in the neck/shoulders are common in children and that understanding the relationship between variables enables valuable elements of measures aimed at maintaining, improving and promoting the welfare of students.